Nonlinear optical properties of liquid crystals and polymer dispersed liquid crystals - Simoni, Francesco (Series on liquid crystals ;, 1997)
This monograph is devoted to a detailed treatment of the nonlinear optical properties of liquid crystals. The basic concepts of director optical reorientation and thermal nonlinearities are presented showing the fundamental theoretical approaches and describing the main experimental observations. The presentation is self-consistent and tutorial although the subject matter is of current research interest. The last part of the book deals with more recent results on new composite materials: Polymer Dispersed Liquid Crystals (PDLC). A general presentation of the optical properties is given and the observations of several nonlinear optical effects are reported.